The 'Wish to Die' in later life: prevalence, longitudinal course and mortality. Data from TILDA. (11th February 2021) - Briggs, Robert; Ward, Mark; Kenny, Rose Anne
Abstract: Background: 'Wish to Die' (WTD) involves thoughts of or wishes for one's own death or that one would be better off dead. Objective: To examine the prevalence, longitudinal course and mortality-risk of WTD in community-dwelling older people. Design: Observational study with 6-year follow-up. Setting: The Irish Longitudinal Study on Ageing, a nationally representative cohort of older adults. Subjects: In total, 8, 174 community-dwelling adults aged ≥50 years. Methods: To define WTD, participants were asked: 'In the last month, have you felt that you would rather be dead?' Depressive symptoms were measured using the CES-D. Mortality data were compiled by linking administrative death records to individual-level survey data from the study. Results: At Wave 1, 3.5% of participants (279/8, 174) reported WTD. Both persistent loneliness (OR 5.73 (95% CI 3.41–9.64)) and depressive symptoms (OR 6.12 (95% CI 4.33–8.67)) were independently associated with WTD. Of participants who first reported WTD at Wave 1 or 2, 72% did not report WTD when reassessed after 2 years, and the prevalence of depressive symptoms (−44%) and loneliness (−19%) was more likely to decline in this group at follow-up. Fifteen per cent of participants expressing WTD at Wave 1 died during a 6-year follow-up. Conclusions: WTD amongst community-dwelling older people is frequently transient and is strongly linked with the course of depressive symptoms and loneliness. An enhanced focus on improving access to mental health care and addressing social isolation in older people should therefore be a public health priority, particularly in the current context of the Covid-19 pandemic.